A Cross-Sectional Study on the Association Between Risk Factors of Toxoplasmosis and One Health Knowledge in Pakistan - Maqsood, Tooba; Shahzad, Khuram; Naz, Shumaila; Simsek, Sami; Afzal, Muhammad Sohail; Ali, Shahzad; Ahmed, Haroon; Cao, Jianping (Frontiers in Veterinary Science, 2021)
Toxoplasmosis is a zoonotic disease caused by Toxoplasma gondii, a protozoan that infects warm-blooded animals and humans. Approximately one third of the global population is infected by T. gondii. We conducted a cross-sectional study to assess the risk factors and One Health knowledge on toxoplasmosis in Rawalpindi and Islamabad, Pakistan. From July through December 2020, we collected data using questionnaires. The results showed that 60% of participants had heard or read about the disease, 23.3% of participants had no knowledge about the disease, and 16.8% participants were not sure about the disease. More than half of the participants (53.3%) reported that toxoplasmosis was caused by toxins, 5.3% reported that toxoplasmosis was an animal disease, 13.8% reported that toxoplasmosis was a human disease, 65.8% reported that it was both an animal and human disease, and 15.3% reported that it was neither an animal nor a human disease. Approximately 80.5% of participants reported that individuals acquired toxoplasmosis by changing cat litter. Our study findings revealed a low level of knowledge and awareness about toxoplasmosis among males. Therefore, there should be awareness programs to educate individuals about the risks of this deadly disease and to provide information on the major routes of transmission.